Corn response to fertilizations based on different soil testing philosopies - Perdomo, C.; Cardellino, G. (Agrociencia Uruguay, 2006)
Corn fertilization in Uruguay is generally based on soil testing, but the existence of various soil testing philosophies could produce a wide range of recommendations of nutrient and rates. The appropriateness of these different approaches can only be assessed by field research covering different soil types and weather conditions. During three crop cycles, comprising from 1999 to 2002, 12 fertilization experiments were established inside commercial corn fields located in the southwest of the country. The treatments consisted of four recommendations of fertilization, two of them originated in Uruguay (URU1 and URU2) and the other two in United States of America (USA1 and USA2). A control treatment without fertilization was also included. The results revealed that in average there was a clear yield response to fertilization. The mean differences among the fertilized treatments, however, were minor (less than 500 kg ha-1), although the “USA” treatments produced a higher mean yield than the “URU” recommendations. The two highest mean net returns to fertilization were obtained with USA2 (182 U$ ha-1) and URU1 (160 U$ ha-1), the treatments which recommended fertilizing with fewer nutrients and lower rates. On the contrary, the treatment USA1, that recommended fertilizing with more nutrients and higher rates, produced the lowest net return to fertilization (104 U$ ha-1). These results suggest that in Uruguayan conditions the most conservative recommendations would tend to produce the best economic results.